The Role of Analysts as Gatekeepers: Enhancing Transparency and Curbing Earnings Management in Brazil - Antonio Lopo Martinez (RAC: Revista de Administração Contemporânea, 2011)
This paper examines the relationship of analysts’ coverage, forecasting errors and earnings management. It corroborates the role of analysts as gatekeepers by finding that analysts enhance transparency and reduce the scope of earnings management. To identify analysts’ coverage we used the I/B/E/S, from where we also obtained information on the consensus projections of analysts for listed Brazilian companies. The results indicated a negative correlation between the number of analysts covering firms and the magnitude of their discretionary accruals in absolute terms, indicating that more scrutiny inhibits earnings management. We also found a negative correlation between analysts’ coverage and forecasting errors. Multivariate regressions showed statistically significant results in the same sense. Therefore, market analysts, despite the severe criticism they receive from the specialized press, actually have a beneficial effect on corporate governance by monitoring managers and inhibiting earnings management.